Required Data for Effective Life-Cycle Management for Transportation Agencies - Giglio, Joseph M.; Friar, John H. (Archives of Business Research, 2023)
Fleet management is the application of processes and systems that ensure equipment is maintained in a state of good repair and reliability, as well as at high availability and at minimum life-cycle costs. One way of doing so is by implementing a methodology known as life-cycle management. A challenge for introducing life-cycle management is identifying what data are needed because collecting, storing, and maintaining the data is expensive. In this paper, we create a comprehensive list of the data an agency could collect in introducing a life-cycle management program. This paper relies on the detailed analysis of a State Department of Transportation as to what it would take to manage the entire life cycle of their mechanical and fleet management services. The paper covers types of data, management reporting frameworks and strategies, and reports. The findings and recommendations resulting from the study are intended to help managers of public agency fleets evaluate available strategies for improving the cost efficiency and service effectiveness of fleet maintenance and management practices within their own organizations.